PERANAN PEMBELAJARAN AKIDAH AKHLAK DALAM MEMBENTUK KARAKTER SISWA DI SEKOLAH DASAR PITTAYAPHAT SUSKA SCHOOL THAILAND - Muhammad Rizky Habibi Hasibuan (ITB AAS Indonesia Surakarta, 2024)
This research was conducted with the aim of understanding the role of Akidah Akhlak learning in shaping student characteristics at Pittayaphat Suska School, as well as factors that influence the application of Akidah Akhlak Learning at Pittayaphat Suska School. This research was conducted using a qualitative approach with a descriptive method. Data is collected through observation of events and processes that are happening. The main data sources are the Principal, Religion Teacher, Subject Teacher, and Students. In implementing this Akidah Akhlak Learning, students are expected to be able to understand Islamic teachings according to the guidelines of the Al-Quran and Hadith to receive various materials and religious knowledge from teachers or ustadz who play a role in teaching this Akidah Akhlak Learning. As for the steps in implementing Akidah Akhlak Learning, the activity begins with reading the Koran together, followed by five daily prayers, duha prayers, and listening to religious lectures together. Keywords: The Role of Learning Aqidah Morals, Character Education of student